Dinamika Reaktor Katalitik Aliran Bolak-Balik untuk Oksidasi Emisi Gas Metana - Budhi, Yogi Wibisono; Rimbuala, Hans Gunawan; Wibisono, Andhika Feri (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2020)
The performance of a reverse flow reactor (RFR) is strongly influenced by the switching time used to alternate the flow direction. This research aimed to study the effect of the switching time on reactor dynamics including the heat propagation along the bed and reaction rate in the oxidation methane for low concentration using catalytic reverse flow reactor. The experimental results show that the reverse flow operating mode can influence heat propagation along the reactor and reaction conversion. Based on the three switching times was tested, the temperature dynamics formed were in the sliding regime. The effect of switching time on RFR on conversion is very significant. When compared to steady operation, RFR operation provides the highest conversion at smaller switching times. At large switching times, the effect of reversal of flow direction becomes less dominant and reactor behavior approaches steady state.